Factors Affecting Fast Food Consumption Behaviors of Female Students in North of Iran: Application of Theory of Planned Behavior - Nooshin Rouhani-Tonekaboni; Seyed Jalil Seyedi-Andi; Mehdi Haghi (Caspian Journal of Health Research, 2018)
Background: Adolescents are the most frequent fast food consumers. This unhealthy behavior lead to overweight that is associated with diabetes mellitus, hypertension, and heart diseases. The present study aimed to determine factors associated with behavior of fast food consumption (FFC) of female high school students based on the Theory of Planned Behavior (TPB) in the city of Tonekanon, north of Iran. Methods: The present cross-sectional study was conducted on 197 female students studying at high school. The constructs of the theory of planned behavior including attitude, subjective norms, perceived behavioral control, as well as intention and behavior of fast food consumption were assessed using a pre-tested psychometric questionnaire. Spearman correlation coefficient and linear regression method were used to test the study hypotheses. Results: The constructs of attitude, subjective norms, and perceived behavioral control were accounted for 37.8% in variation of fast food consumption intention.  The construct of subjective norms and perceived behavior control was significantly associated with intention of FFC. Intention of FFC was significantly associated with behavior (B coefficient = 0.76, P-value = 0.001) and predicted 63.8 % of the variance of fast food consumption behavior. Conclusion: The present study showed that the TPB is a powerful theory in predicting FFC behavior. Subjective norms followed by perceived behavioral control were the strongest predictors of FFC intention.